Increasing women’s empowerment: Evaluating two interventions in Uganda - Ambler, Kate; Jones, Kelly M.; O’Sullivan, Michael (Elsevier, 2026)
We conduct a randomized controlled trial to test a novel intervention for increasing women’s empowerment in Uganda. The intervention includes a within-household transfer of a productive asset, which has a lower cost than an external transfer. We find that transferring control of some of the household’s sugarcane to the wife significantly increases her access to resources and decision-making power. We also document increases in women’s empowerment arising from a cross-randomized couples’ workshop that improved women’s self-concept and shifted beliefs in gender equality. We find no additional impacts from combining the two interventions. Importantly, neither intervention harms the household’s productivity or husbands’ welfare. In fact, men (and women) report higher marital quality and life satisfaction as a result. However, despite increasing women’s empowerment we find no evidence that the interventions increased measured household investment in food security, child health, or education.